2010
DOI: 10.1007/s12665-010-0457-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the degree of contamination and evolution in the last 100 years of the composition of the bed sediments of the Anllóns Basin

Abstract: In this study, five cores of the Anllóns River bed sediments were analyzed in order to evaluate the downcore and downstream variations in their chemical composition. The first step was the evaluation of the metal distribution in the bulk (\2 mm) and fine fractions (\63 lm). The analysis revealed that most of the metals followed the same trend in both fractions, although the fine fraction presented usually higher concentrations. However, the concentration of both fractions tended to equalize with increasing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…These authors identified urban land use and population density as more important influences on the bed sediment chemistry. Similar patterns have been observed in previous studies in the Anllóns basin, on nutrients (DevesaRey et al 2009) and metals (Devesa-Rey et al 2010), in which no consistent increase was observed along the watercourse. Rather, fluctuations occurred in response to the proximity of pollution sources or changes in the water flow.…”
Section: Evaluation Of Total Phosphorus Concentrations In the Soil Ssupporting
confidence: 91%
“…These authors identified urban land use and population density as more important influences on the bed sediment chemistry. Similar patterns have been observed in previous studies in the Anllóns basin, on nutrients (DevesaRey et al 2009) and metals (Devesa-Rey et al 2010), in which no consistent increase was observed along the watercourse. Rather, fluctuations occurred in response to the proximity of pollution sources or changes in the water flow.…”
Section: Evaluation Of Total Phosphorus Concentrations In the Soil Ssupporting
confidence: 91%
“…Additionally, most of metals follow the same trend in both fractions, indicating that both are affected by the same sources of contamination, although in a different degree. The same trend was also observed by Devesa-Rey et al (2010b) in the Anllóns River (Spain).…”
Section: Origin and Intensity Of The Contaminationsupporting
confidence: 81%
“…), is 516 km 2 (Devesa‐Rey et al ) and drains a predominately igneous and metamorphic hinterland (Arribas et al ). The dominant land uses are pastoral and arable agriculture and forestry (Devesa‐Rey et al ; Costas et al ). There are two towns in the region, Carballo and Ponteceso, and a small coastal town at Laxe.…”
Section: Study Areamentioning
confidence: 99%
“…The Anllóns River flows downstream into the Anllóns Estuary, where it passes into the Ría de Corme y Laxe and then into the mid‐Atlantic Ocean (Costas et al ). The river is approximately 60 km in length and is undammed (Devesa‐Rey et al ). The average flow of the river is 11.9 m 3 s −1 which can vary at the extreme between 80 m 3 s −1 and 1 m 3 s −1 from the wet season to the dry season (Varela et al ; Costas et al ).…”
Section: Study Areamentioning
confidence: 99%